Tendências das perspectivas Ciência, Tecnologia e Sociedade (CTS) nas áreas de educação e ensino de ciências: uma análise a partir de teses e dissertações brasileiras e portuguesas - Miranda, Elisangela Matias (2012)
Nowadays, Science and Technology developments and influences on humanistic, social, cultural and economic dimensions have raised discussions about the nature, potential and limits of those areas. Science teaching according to STS (Science-Technology-Society) education comes out as an approach that aims to integrate scientific, technological and social themes in a given content. This approach stimulates students to develop skills that enhance their ability to play their role in society in an active and mindful manner, and hence contributes to the rise of a larger number of scientifically and technologically literate citizens. In that regard, the main objective of the present study is to analyze academic studies master s and doctoral theses produced between 1992 and 2009 that have focused on the STS education field, seeking to identify STS education perspectives pointed out in those studies during that time span. The secondary objectives of this study are: (i) to identify master s and doctoral theses in Education, Science and Mathematics Teaching or related graduate programs of Brazilian and Portuguese federal or state universities, all of the works dating from 1992 to 2009 and investigating approaches related to STS education; and (ii) to characterize the thematic focuses, methodological and STS approaches in those theses. Therefore, this is a state of knowledge research conducted according to a theoretical, bibliographical, and quantitative-qualitative approach, for which the Qualitative Content Analysis method was used. Among the most relevant results, it has been found that 14% of the investigated Brazilian theses were directed towards the college level, whereas none of the Portuguese theses had the same intent. On the other hand, 79% of the Portuguese theses were aimed to the first years of school, whereas only 21% of the Brazilian theses were devoted to that education level. Analyses were also carried out in order to identify and discuss which STS approaches and/or perspectives are present in doctoral theses finished at both Brazilian and Portuguese universities. Such analyses have indicated that the main STS education model observed in the theses is Logical reasoning (40% of the theses, i.e., 10 out of 24 theses), followed by Sociocultural (39% of the theses, i.e., 9 out of 24 theses), Historical (3 theses), Socio-ecojustice (2 theses), and Application/Design (1 thesis). In general, the analyzes revealed that, even though there is a consensus among the academic community involved with studies on STS education, different interpretations of STS-based Science education have been emerging along decades, which reveals a field under construction and reconstruction.